Conceptualization of Legal Terms in Different Fields of Law: The Need for a Transparent Terminological Approach - Bajcic, Martina (Research in Language, 2011)
Researchers often use subject-specific terminology in order to facilitate communication within a given field of law. Difficulties may arise when they must use scientific information that does not belong to their field. The transfer of information from one subject area to another is restricted by the technical vocabulary used in the particular field. If this is so, what happens when lawyers in one field of law use terms from another? Is the concept in question couched in the same term within another field of law as well? The process of conceptualizing one and the same legal term in different legal fields does not always proceed smoothly. As will be illustrated in this paper, the problem of conceptualizing legal terms in different fields of law calls for a transparent terminological approach. While it is true that legal concepts cannot be fully conveyed by terminology, a transparent terminological approach can contribute to the understanding of these concepts and facilitate their use in legal comparisons, thus making such an approach a conditio sine qua non of legal translation.